(untitled) (UNED Research Journal, 2019)
Introduction: historically there have been difficulties in learning basic physics concepts as well as high levels of reprobation in these introductory courses at university. The Instituto Tecnológico de Costa Rica (TEC) is not the exception and therefore the initiative to innovate in education arises. Objective: to describe an experience in the implementation of active methodologies in teaching in Physics (Peer Instruction and Just in Time Teaching) as well as its scope in the academic performance of students who study General Physics; it is based on the assumption that a transformation in the pedagogical approach of the lessons can affect student performance. Methods: we analyzed the results of those who were taught through these active methodologies compared to those who were exposed to lectures. Results: we found significant improvements (F(1-59)=9,637, p=0,002) in the exam performance of students exposed to active methodologies Mean grade=64,3), in comparison to those who received lectures (Mean grade=54,5). Conclusion: It is necessary that both teachers and institutions stop assuming that all teachers possess the cognitive skills that facilitate a gain in student learning without adequate training.